French E-Module for Production Écrite Débutante Learning Based on Project Based Learning Using Kodulars - Marice; Isda Pramuniati; Jubliana Sitompul (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Students need help with ideas and writing simple sentences in French according to the correct rules. In addition, the learning media used are still dominated by conventional methods such as printed books and sheets of paper, which are less exciting and do not support the learning process effectively. This study aims to design project-based learning (PjBL)-assisted Kodular e-module for French Production Écrite Débutante (writing for beginners). The research method used the Research and Development (R&D) method of the ADDIE model. The subjects involved in this study were 16 students. The data collection methods used were observation and questionnaires. The instrument used was a questionnaire sheet. After the data was collected, it was analyzed using qualitative and quantitative data analysis methods. The results showed that the E-Module that had been developed was adequate for beginners to use in learning French writing. Thus, it can be concluded that the E-Module that has been created is feasible and effective for beginners to use in learning French writing. The use of e-modules assisted by Codular application in learning writing based on Project Based Learning (PjBL) can be an innovative solution to improve students' writing skills.